2011
DOI: 10.1002/ajmg.a.34268
|View full text |Cite
|
Sign up to set email alerts
|

Fetal akinesia in metatropic dysplasia: The combined phenotype of chondrodysplasia and neuropathy?

Abstract: Dominant mutations in the receptor calcium channel gene TRPV4 have been associated with a family of skeletal dysplasias (metatropic dysplasia, pseudo-Morquio type 2, spondylometaphyseal dysplasia, Kozlowski type, brachyolmia, and familial digital arthropathy) as well as with dominantly inherited neuropathies (hereditary motor and sensory neuropathy 2C, scapuloperoneal spinal muscular atrophy, and congenital distal spinal muscular atrophy). While there is phenotypic overlap between the various members of each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…20 The three mutations identified in the fetuses and newborn with fetal akinesia and metatropic dysplasia were G78W in the N-terminal domain, K276E in finger loop 3 of the ARD and T740I in the C-terminal domain. 21 All three are novel as they have not been reported in any of the previously identified individuals with metatropic dysplasia. Finally Unger et al 21 refer to a manuscript in press by Cho et al detailing the finding of features of a neuropathy in a patient with SMDK and a mutation already documented in association with this phenotype (Cho et al mutation not revealed).…”
Section: Axonal Neuropathy Compared To Skeletal Dysplasiamentioning
confidence: 95%
See 2 more Smart Citations
“…20 The three mutations identified in the fetuses and newborn with fetal akinesia and metatropic dysplasia were G78W in the N-terminal domain, K276E in finger loop 3 of the ARD and T740I in the C-terminal domain. 21 All three are novel as they have not been reported in any of the previously identified individuals with metatropic dysplasia. Finally Unger et al 21 refer to a manuscript in press by Cho et al detailing the finding of features of a neuropathy in a patient with SMDK and a mutation already documented in association with this phenotype (Cho et al mutation not revealed).…”
Section: Axonal Neuropathy Compared To Skeletal Dysplasiamentioning
confidence: 95%
“…21 All three are novel as they have not been reported in any of the previously identified individuals with metatropic dysplasia. Finally Unger et al 21 refer to a manuscript in press by Cho et al detailing the finding of features of a neuropathy in a patient with SMDK and a mutation already documented in association with this phenotype (Cho et al mutation not revealed). 21 These observations together suggest that mutations at the four key residues in the ARD mentioned above cause a neurological disorder with probably secondary skeletal changes.…”
Section: Axonal Neuropathy Compared To Skeletal Dysplasiamentioning
confidence: 95%
See 1 more Smart Citation
“…Sometimes metatropic dysplasia is combined with lethal fetal akinesia. The nonlethal forms are characterized by short limbs, shortening of all long bones, enlargement of joints, severe kyphoscoliosis, severe platyspondyly, severe metaphyseal enlargement, and defects in ossification (Krakow et al, 2009;Camacho et al, 2010;Unger et al, 2011).…”
Section: Trp Channels As Drug Targetsmentioning
confidence: 99%
“…al., 2010; Unger et al, 2011;Cho et al, 2012;Evangelista et al, 2015]. TRPV4 mutations are inherited in a dominant/heterozygous manner, and the clinical phenotype tends to be similar in families.…”
mentioning
confidence: 99%